Control of carbendazim toxicity using banana peel powder in rats - Gomaa N. Abdel-Rahman; Ahmed S.M. Fouzy; May M. Amer; Essam M. Saleh; Islam A. Hamed; Bassem A. Sabry (Biotechnology Reports, 2022)
Carbendazim (CBZ) is a steady benzimidazole fungicide broadly exploited in cultivation for pre- and post-harvest treatment to dominate microorganisms infection on several plants. CBZ causes toxic effects in the different tissues of rat via influencing biochemical and hematological factors causing histopathological alterations in the liver and kidney of rats. Banana peel (BP) makes up about 38% of the whole banana weight, BP is usually disposed of as waste that is considered as an environmental problem. BP comprise bioactive a lot of compounds that can be exploited for their unique biological and pharmacological attributes. The current study was carried out to determine the protective effect of dried banana peels consumption against carbendazim toxicity in rats. The results indicated that banana peels had the ability to counteract the toxic effect of carbendazim on rats which was evident by the improvement in liver and kidney functions, lipid profile and histopathological examination.